Molecular characteristics, risk factors, and clinical outcomes of methicillin-resistant Staphylococcus aureus infections among critically ill pediatric patients in Shanghai, 2016–2021 - Dai, Congyi; Ji, Wenting; Zhang, Yufei; Huang, Weichun; Wang, Haiying; Wang, Xing (Frontiers in Pediatrics, 2024)
Objective Methicillin-resistant Staphylococcus aureus (MRSA) infection in children has been on the rise, which poses a serious threat to their health and life in China. The purpose of this study was to determine the molecular characteristics, risk factors, and clinical outcomes of MRSA infections among critically ill pediatric patients.Methods A retrospective case-control study was performed in the pediatric intensive care unit (PICU) of a tertiary university teaching hospital. All children infected with culture-positive S. aureus in the PICU between January 2016 and December 2021 were included. Univariate and multivariable logistic regression analyses were used to identify potential risk factors for MRSA infection and clinical outcomes of S. aureus infection. All S. aureus isolates were characterized based on antimicrobial resistance, multilocus sequence typing (MLST) and Staphylococcal protein A (spa) typing.Of 3974 patients admitted to the PICU, 280 were diagnosed with a S. aureus infection during the 6-year study period. Among them, 43.2% (121/280) were MRSA. All MRSA isolates showed significantly higher rates of resistance to penicillin, erythromycin, clindamycin and tetracycline than MSSA strains. The MRSA strains consisted of 45 spa types and 20 sequence types (STs) (20 clonal complexes), among which the most frequently represented were ST59-t437and ST398-t034. Multivariable logistic regression revealed vaginal delivery, respiratory failure, co-infection with a virus, C-reactive protein (CRP) > 8 mg/L as significant risk factors for MRSA infection. There was no significant difference in all-cause mortality during hospitalization between the MRSA group and the MSSA group. Furthermore, independent predictors for mortality in patients with S. aureus infections were the presence of hypoproteinemia, hematopathy, septic shock, respiratory failure, fever, and white blood cell (WBC) > 15.0× 10 9 /L.The study revealed a high proportion of MRSA infections among critically ill pediatric patients, and found significant risk factors for MRSA infection and poor prognosis of S. aureus infection. Methicillin resistance did not contribute to the mortality in the current study. These findings will provide evidence-based practices to make the strategies of prevention and rational use of antibiotics for pediatric patients with S. aureus infection in the ICU.